2018
DOI: 10.1145/3241046
|View full text |Cite
|
Sign up to set email alerts
|

Detection Mechanisms for Unauthorized Wireless Transmissions

Abstract: With increasing diversity of supply chains from design to delivery, there is an increasing risk that unauthorized changes can be made within an IC. One of the motivations for this type of change is to learn important information (such as encryption keys, spreading codes) from the hardware, and transmit this information to a malicious party. To evade detection, such unauthorized communication can be hidden within legitimate bursts of transmit signal. In this article, we present several signal processing techniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Two HT payload mechanisms are shown in [29], one that uses a single pole double throw switch and a pair of resistors to alter the input termination impedance of the power amplifier, and another one that reprograms the gain stages. In [28], it is proposed to use spread spectrum techniques to hide an unauthorized transmission signal within the legitimate signal below the noise level. For all the aforementioned HT attacks, the IC passes all conventional specification tests and the transmission signal still obeys the transmission specifications and is within the margins allowed because of process variations.…”
Section: Prior Art On Ht Attacks In the Analog Domainmentioning
confidence: 99%
See 1 more Smart Citation
“…Two HT payload mechanisms are shown in [29], one that uses a single pole double throw switch and a pair of resistors to alter the input termination impedance of the power amplifier, and another one that reprograms the gain stages. In [28], it is proposed to use spread spectrum techniques to hide an unauthorized transmission signal within the legitimate signal below the noise level. For all the aforementioned HT attacks, the IC passes all conventional specification tests and the transmission signal still obeys the transmission specifications and is within the margins allowed because of process variations.…”
Section: Prior Art On Ht Attacks In the Analog Domainmentioning
confidence: 99%
“…However, the attacker knowing the HT payload mechanism can listen to the channel and recover the key. It has been demonstrated that this type of HTs can be detected by statistical side-channel fingerprinting [27], careful analysis of the transmitted signal spectrum [28], or adaptive channel estimation [29], which leverages the slowfading characteristics of indoor communication channels to distinguish between channel impairments and HT activity.…”
Section: Prior Art On Ht Attacks In the Analog Domainmentioning
confidence: 99%
“…Several studies have demonstrated this type of HT attack. The HT can be embedded within the Medium Access Control (MAC) protocol [22], within the digital baseband physical layer (PHY) [23], [24], [25], [26], [27], or its payload mechanism can partially act upon the Analog Front-End (AFE) [28], [29], [30], [31], [32]. In parallel, these studies propose defenses for detecting the HT attack at test time or during run-time.…”
Section: Introductionmentioning
confidence: 99%
“…cipher keys. It has been demonstrated how the key can be encoded into minute differences in amplitudes or frequencies of the transmitted signal [11], [12] or into an unauthorized transmission signal that is hidden within the legitimate signal [13]. In both cases, the IC passes all conventional specification tests and the transmission signal still obeys to the transmission specifications and is within the margins allowed because of process variations.…”
Section: Introductionmentioning
confidence: 99%
“…However, the attacker knowing the HT payload mechanism can listen to the channel and recover the key. It has been demonstrated that this type of HTs can be detected by statistical fingerprinting [11], [12], careful analysis of the transmitted signal spectrum [13], or channel estimation [14]. Another interesting direction for HT design is to exploit the fact that an analog IC may have undesired states or operation modes [15].…”
Section: Introductionmentioning
confidence: 99%